PRO-Mueve Relaciones Sanas – A Gender-Based Violence Prevention Program for Adolescents: Assessment of Its Efficacy in the First Year of Intervention - Velasco, Lilian; Thomas-Currás, Helena; Pastor-Ruiz, Yolanda; Arcos-Rodríguez, Aroa (Frontiers in Psychology, 2022)
PRO-Mueve Relaciones Sanas (PRO-Mote Healthy Relationships) is a gender-based violence and dating violence prevention program targeted at adolescents. The program has been designed to be implemented during three consecutive courses (from the first to third year of Spanish mandatory secondary education [ESO]) in 8 annual sessions, imparted by university students who have been previously trained and supervised by university professors. The present study evaluates the effects of the program after the first year of implementation through a quasi-experimental design (Intervention Group N=181; Quasi-control group N=62; Mage= 12.11; SDage=0.57; 54.7% girls) and assesses whether there are gender differences in the outcomes. The results obtained evidenced a significant reduction in benevolent sexism in the intervention group compared to the quasi-control group. Regarding hostile sexism, it was found to increase significantly in the quasi-control group, while it remained stable in the intervention group. Thus, there were significant differences between both groups after the intervention. Likewise, romantic love myths were found to decrease significantly, and knowledge about gender-based violence increased significantly in the intervention group between the two time points assessed, although there were no significant differences with the quasi-control group. No gender differences in the outcomes of the program were observed. The obtained results supported the efficacy of the program during the first year of intervention in the first course of the ESO and laid the foundation for the following phases of intervention.